The Relationship between the Level of Nutritional Knowledge and Physical Activity on the Nutritional Status of Volleyball Athletes at the Attack Volleyball Club Samarinda - Risky Syahbannur; Supriadi B; Rieska Indah Mulyani; Lamri (Formosa Journal of Science and Technology, 2023)
The need for nutrients in the world of sports is an important factor in supporting athlete performance. At present the related attention regarding the regulation of good food for athletes is still lacking. Nutritional issues are very important in achieving sports achievements. This study aims to analyze the relationship between the level of nutritional knowledge and physical activity on the nutritional status of volleyball athletes at the Attack Volley Ball Club Samarinda. The research design was cross-sectional involving 34 Attack Volley Ball Club Samarinda athlete respondents. Data were analyzed using Fisher Exact Test. The results showed that there was no significant relationship between nutritional knowledge and nutritional status (p-value = 0,116), then there is no significant relationship between physical activity and nutritional status  (p-value  = 0,125).